Indirect Estimates of Jaw Muscle Tension in Children With Suspected Hypertonia, Children With Suspected Hypotonia, and Matched Controls. (Journal of Speech, Language & Hearing Research, 2013)
Purpose: In this study, the authors compared indirect estimates of jaw-muscle tension in children with suspected muscle-tone abnormalities with age- and gender-matched controls. Method: Jaw movement and muscle activation were measured in children (ages 3 years, 11 months, to 10 years) with suspected muscle-tone abnormalities (Down syndrome or spastic cerebral palsy; n = 10) and controls (n = 11). Two measures were used to infer jaw tension: a kinematic index of mass-normalized stiffness and electromechanical delay (EMD). The kinematic index used video-based kinematics to obtain the slope of the peak velocity displacement relationship. The EMD was derived from the interval between the onset of suprahyoid muscle activity and the onset of jaw depression. Results: Neither measure differentiated the groups. The kinematic index revealed differences between stressed and unstressed syllables in 3-syllable productions by the participants with cerebral palsy and controls, but not in 2-syllable productions by the participants with Down syndrome and controls. Conclusion: This preliminary investigation included the novel application of 2 measures to infer the jaw-muscle tension of children with suspected tone abnormalities. Although the results do not support the hypothesis that suspected muscle-tone abnormalities affect jaw movement sufficiently to influence speech production, considerations for interpreting the findings include methodological limitations and possible compensatory muscle coactivation.